2014
DOI: 10.1093/hmg/ddu102
|View full text |Cite
|
Sign up to set email alerts
|

Monozygotic twins discordant for recessive dystrophic epidermolysis bullosa phenotype highlight the role of TGF-β signalling in modifying disease severity

Abstract: Recessive dystrophic epidermolysis bullosa (RDEB) is a genodermatosis characterized by fragile skin forming blisters that heal invariably with scars. It is due to mutations in the COL7A1 gene encoding type VII collagen, the major component of anchoring fibrils connecting the cutaneous basement membrane to the dermis. Identical COL7A1 mutations often result in inter- and intra-familial disease variability, suggesting that additional modifiers contribute to RDEB course. Here, we studied a monozygotic twin pair w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 64 publications
7
112
0
8
Order By: Relevance
“…TGF-β signaling leads to phosphorylation of downstream effector SMAD proteins, of which, activated SMAD3/4 bind to COL7A1 promoter and promote COL7A1 transcription. Furthermore, TGF-β activation influences RDEB disease severity through increased type 1 collagen and decreased decorin expression (Odorisio et al , 2014). Previous studies have also demonstrated that TGF-β signaling results in a decrease in miR-29 expression through inhibition of transcription via binding of SMAD3 to the miR-29 promoter region (Qin et al , 2011, Zhou et al , 2012).…”
Section: Resultsmentioning
confidence: 99%
“…TGF-β signaling leads to phosphorylation of downstream effector SMAD proteins, of which, activated SMAD3/4 bind to COL7A1 promoter and promote COL7A1 transcription. Furthermore, TGF-β activation influences RDEB disease severity through increased type 1 collagen and decreased decorin expression (Odorisio et al , 2014). Previous studies have also demonstrated that TGF-β signaling results in a decrease in miR-29 expression through inhibition of transcription via binding of SMAD3 to the miR-29 promoter region (Qin et al , 2011, Zhou et al , 2012).…”
Section: Resultsmentioning
confidence: 99%
“…As a result of reduced TGF-β activity, there was significantly slower progression to fibrotic digit fusion and mitten deformities (76). The role of TGF-β signalling has been highlighted as a potential modifier of disease severity following the study of monozygotic twins with RDEB with markedly different clinical phenotypes and similar amounts of C7 expression (77). In this study, genome wide expression analysis in twins' fibroblasts showed differential expression of the genes associated with TGF-β pathway inhibition.…”
Section: Systemic Treatmentmentioning
confidence: 73%
“…Deficiency of the ECM protein C7 in DEB leads to substantial dermal changes: impaired skin regeneration and TGF--driven fibrosis that facilitates aggressive squamous cell carcinoma (SCC) (8)(9)(10)12,38,40). However, C7 is both a dermal and an epidermal product and so far the direct cellular changes that loss of C7 evokes in epidermal keratinocytes remained limitedly studied (7,38).…”
Section: Discussionmentioning
confidence: 99%
“…It has become apparent that progressive TGF--mediated soft tissue fibrosis plays a major role in disease evolution of DEB (11,12). In other diseases epithelial dysfunction is known to be a major instigator of fibrosis (13).…”
Section: Introductionmentioning
confidence: 99%